Cropping systems diversification, improved seed, manure and inorganic fertilizer adoption by maize producers of eastern Ethiopia - Musa Hasen Ahmed; Kassahun Mamo Geleta; Aemro Tazeze; Hiwot Mekonnen Mesfin; Eden Andualem Tilahun (Journal of Economic Structures, 2017)
The gap between demand for and supply of food in Ethiopia can be reduced by improving farm productivity through the introduction of productivity-enhancing technologies. Conversely, in Ethiopia, the adoption rates of agricultural technologies remain below the expected levels. Hence, by using multivariate probit model, this study identifies factors that motivate the adoption of a combination of inorganic fertilizer, improved seed, manure and cropping system diversification in eastern Ethiopia using multiple plot-level observations. The analysis shows that the probabilities of adoption of agricultural technologies are influenced by household, socioeconomic, institutional and plot-level characteristics. Alongside this, the paper also shows that there is a significant correlation between the selected technologies, suggesting that adoptions of technologies are interrelated. Specifically, the result indicates that there is complementarity between inorganic fertilizer and improved seed; and substitutability between inorganic fertilizer and manure. The result also indicates there is complementarity between adoption of improved seed and manure; and adoption of improved seed and crop diversification.
Keywords: Q01; Q12; Q16; Q18; 330; Adoption; Multiple technologies; MVP; Maize; Ethiopia